Observer Reactions to Workplace Mistreatment: It’s a Matter of Perspective - Reich, T.C.; Hershcovis, M.S.; Lyubykh, Z.; Niven, K.; Parker, Sharon; Stride, C.B. (EDUCATIONAL PUBLISHING FOUNDATION-AMERICAN PSYCHOLOGICAL ASSOC, 2021)
Workplace mistreatment regularly occurs in the presence of others (i.e., observers). The reactions of observers toward those involved in the mistreatment episode have wide-reaching implications. In the current set of studies, we draw on theories of perspective-taking to consider how this form of interpersonal sensemaking influences observer reactions toward those involved in a witnessed incident of workplace mistreatment. We find that observers’ blame attributions and empathic concern for the individual whose perspective is taken explain the positive effects of perspective-taking on observer attitudes toward and performance evaluations of both the target and instigator of a witnessed incident of mistreatment. We also find that the effect of perspective-taking on observer reactions is stronger when the witnessed mistreatment is more severe. Finally, we find that although observer perspective-taking in the context of mistreatment can be encouraged, the effect seems to benefit instigators’ performance evaluations rather than targets’. Implications for targets, instigators, and organizations are discussed.